From Data to Decision-Making: The Development of Statistical Literacy Among Pre-Service Primary School Teachers Through Contextual Learning - Melda Jaya Saragih; Kurnia Putri Sepdikasari Dirgantoro; Robert Harry Soesanto; Tanti Listiani (Universitas Sultan Ageng Tirtayasa, 2026)
Prospective teachers need to have good statistical literacy because they will become a decision-makers in data-based classroom learning. They must be able to determine when to change learning according to students’ progress. Prospective teachers, including Primary Student Teacher Education (PGSD) are not only able to do statistical calculations, but also as the ability to read data, interpret statistical information, and use the analysis data results as a basis for rational and responsible decision-making. This study aims to examine student statistical literacy development through contextual learning. The study used a quantitative approach with a one group pretest–posttest design, involving 72 PGSD students at one of the private universities in Indonesia. The instrument is a statistical literacy essay test. The data was analyzed using the Wilcoxon Signed Rank Test. The results showed a significant increasing in statistical literacy after the implementation of contextual learning. These findings confirm that contextual learning is effective in improving students' statistical literacy and is recommended as a pedagogical approach to strengthen the statistical literacy of prospective teachers.